(3CfhGQ GdWdYI aj ePGgH GdbQGA GdSHYIs - (3eMeO Hf CMeO GdThHQj GdTGaYj GdeUQj, TeS GdOjf,J (B1069 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdabjQ Edi ehdGg GdZfj Hg YeG ShGg CMeO Hf eMeO GdThGHQj bO SCdfj HYV GdENhGf ef Cgd GdUaG hGdYQaGf s
(3BNQgG (B:s
(3hEfj SCdJ Gddg JYGdi aj Chd EHJOGj aj gPG GdoeNJUQ GdeHGQc Cf jfaY Hg cd ef WdYg Ch fXQ ajg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B11 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B257s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs